New Zealand medievalism
1 online resource (xii, 224 pages).
Keywords: "This volume maps the phenomenon of medievalism in Aotearoa, initially as an import by the early white settler society, and as a form of nation building that would reinforce Britishness and ancestral belonging. This colonial narrative underpins the volume's focus on the imperial relationship in chapters on the academic study of the Middle Ages, on medievalism in film and music, in manuscript and book collections, and colonial stained glass and architecture. Through the alternative 21st century frameworks of a global Middle Ages and Aotearoa's bicultural nationalism, the volume also introduces Maori understandings of the ancestral past that parallel the European epoch and, at the opposite end of the spectrum, the phenomenon of global right-wing medievalism, as evidenced in the alt-right extremism underpinning the Christchurch mosque attack of 2019. The volume will appeal to educationists, scholars, and students interested in the academic history of the Middle Ages in New Zealand; enthusiasts of film, music, and performance of the medieval; members of the public interested in Aotearoa's history and popular culture; and all who enjoy the colourful reinventions of medievalism"--